TRIGGERS OF MUHAMMADIYAH TEACHERS COMMITMENT TO DEVELOP THE QUALITY OF SCHOOL - Sukirman, Sukirman (Universitas Pendidikan Indonesia, 2019)
This study aims to look at various components triggering the commitment of Muhammadiyah teachers in developing the quality of Muhammadiyah schools. This research uses a quantitative method involving 60 elementary school teachers with a varied work period. The analysis used is multiple regression analysis to measure the independent variable on the dependent variable. The results of this study state that the relative advantage, compatibility, trialability, ease of development, ease of work, result demonstrability, image, and voluntariness variables can predict the commitment of teachers in developing the quality of Muhammadiyah elementary schools with an F value of 23,717 and a probability value of 0,000 . Meanwhile, of the eight variables, only the compatibility and voluntariness variables have a significant influence with the probability values of 0.036 and 0,000.